2008
DOI: 10.1177/002204260803800412
|View full text |Cite
|
Sign up to set email alerts
|

Getting Huge, Getting Ripped: A Qualitative Exploration of Recreational Steroid Use

Abstract: Steroid use is only now being recognized as a national epidemic. Although American athletes have been using anabolic steroids since the 1950s, it was not until the 1980s that athletic governing bodies began to monitor and sanction illegal supplementation. It is easier to understand why paid, professional athletes might partake in steroid use; keeping up with the competition, sustaining or improving abilities, salary incentives and endorsements based on performance are but a few reasons. But it is more difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 46 publications
1
32
0
2
Order By: Relevance
“…Importantly in this respect, the exact extent and severity of harms caused by the self-administration of anabolic steroids has never been quantified (Pope et al, in press). In addition, the denial of the efficacy of anabolic steroids followed by unsupported health warnings about the harms of anabolic steroids has resulted in barriers to credibility and trust (Dawson, 2001;Grogan et al, 2006;Petrocelli et al, 2008). It is paramount therefore to gauge more accurately the risks of anabolic steroid usage in order to being able to provide users with unambiguous advice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly in this respect, the exact extent and severity of harms caused by the self-administration of anabolic steroids has never been quantified (Pope et al, in press). In addition, the denial of the efficacy of anabolic steroids followed by unsupported health warnings about the harms of anabolic steroids has resulted in barriers to credibility and trust (Dawson, 2001;Grogan et al, 2006;Petrocelli et al, 2008). It is paramount therefore to gauge more accurately the risks of anabolic steroid usage in order to being able to provide users with unambiguous advice.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of studies into body image satisfaction, it has been shown that body dissatisfaction, along with the desire to enhance muscularity, can prompt the use of anabolic steroids in men (Grogan, 2008). The few existing qualitative studies show that users exchange anabolic steroid-related knowledge and will often defer to opinion leaders (sometimes referred to as 'steroid gurus') 4 and more experienced steroid users (Petrocelli et al, 2008). This knowledge, based predominantly on personal experience and anecdotes, includes information on methods to reduce or avoid adverse effects (Monaghan, 2001).…”
Section: Background Literaturementioning
confidence: 99%
“…D'après les résultats présentés, il semble que les effets secondaires des stéroïdes anabolisants soient très diversifiés, touchant plusieurs organes et étant souvent irréversibles (Kanayama et al, 2008, Kutscher et al, 2002Mottram & George, 2000;Petrocelli et al, 2008). Le système cardiovasculaire est celui le plus souvent affecté et qui peut engendrer des effets à d'autres systèmes, tel le foie et les reins.…”
Section: Discussionunclassified
“…Certains de ces effets disparaissent lorsque l'utilisation des stéroïdes est arrêtée mais d'autres persistent. Selon quatre revues de la littéra-ture sur les stéroïdes anaboliques, voici quelques uns des effets néfastes, mais tous ne sont pas encore prouvé scientifiquement ou a été observé dans de rare cas et d'autres recherches devraient être entreprises (Kanayama et al, 2008;Kutscher et al, 2002;Mottram & George, 2000) : (Kanayama et al, 2008;Kutscher et al, 2002;Mottram & George, 2000;Petrocelli et al, 2008)  Chez les femmes : hirsutisme, acné, aggravation de la voie, hypertrophie du clitoris, diminution de la masse des seins, diminution de la menstruation, augmentation de l'appétit, calvitie (Kutscher et al, 2002) Notre revue de la littérature nous a informée sur ces diffé-rents effets néfastes sur la santé :…”
Section: Résultatsunclassified
“…Several studies have documented both the increase in the amount consumed and in the variety of new formulations. However, in the last fifteen years, patterns of recreational steroid use have emerged outside the sphere of competitive sport (Agulló et al 2008;Petrocelli et al 2008;Breivík et al 2009;Bojsen-Møller and Christiansen 2010;Rosenberg and Rodríguez 2010;Christiansen and Bojsen-Møller 2012;Agulló-Calatayud 2013).…”
Section: Introductionmentioning
confidence: 99%